Issue analysis of contracts termination in Russian state and municipal public procurement procedures - A. Ya. Geller (Вестник университета)
The article points out the problem of quality of interaction between the customer and the supplier of goods, works or services in the sphere of state and municipal public procurement procedures of Russian Federation. One of the manifestations of the problem is the high percentage of contract termination between procurement participants (approximately 20 % of the number of contracts concluded). The objective of the study was to suggest potential directions for improving the quality of interaction between procurement participants, against the background of considering the legal grounds for contracts termination. Based on the results of the study, the author identified the problem of lack of technics in the procurement control process, which reduce consequences of the uncertainty external environment impact and fair risk responsibility sharing of non-performing contract liabilities between the procurement participants.